POTENTIAL USE OF Ulva lactuca AS FEED INGREDIENT FOR TILAPIA - Nur Hikma Mahasu; Dedi Jusadi; Mia Setiawati; I Nyoman Adi Asmara Giri (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Due to the mainly imported for fish feed ingredients in Indonesia, many attemps have been made to discover local potential ingredients to reduce the utilization of imported ingredients. In this experiment, the utilization of Ulva lactuca as feed ingredient for tilapia was evaluated. Experiment 1 was conducted to determine the digestibility of Ulva for tilapia. In experiment 2 and 3, Ulva was used to substitute wheat pollard of either 0, 3, 6, 9, or 12 % in the feed formulation. In experiment 2, fish with an average body weight of 4.1±0.15 g were fed on those diets, and were cultured for 55 days. To calculate the digestibity in experiment 3, Cr2O3 was added into the diet of exeriment 2; then fed on the fish with an average body weight of 19.0±0.67 g. Results showed that apparent digestibility of dry matter and crude protein of Ulva were 66.3 and 83 %, respectively. Ash content in the diet increased of 13.5% with Ulva inclusion of 12%. On the other hand, using Ulva as a substitute for pollard up to 12% was not affected the growth performance of fish. Regardless of the Ulva level in the diet, the digestibility of the diet was the same. Therefore, Ulva is a potential source of local feed ingredient for tilapia. Keywords: Ulva lactuca, tilapia, digestibility, growth